2017
DOI: 10.1002/jca.21600
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of acquired Thrombotic Thrombocytopenic Purpura in the U.S. remains heterogeneous: Current and future points of clinical equipoise

Abstract: Treatment of acquired TTP in the U.S. remains heterogeneous. Points of clinical equipoise identified were PV exchanged (1.0 vs >1.0), tapering of TPE versus none, and rituximab use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
1
14
0
1
Order By: Relevance
“…Rituximab is commonly used to treat mainly refractory and relapsed iTTP patients 10 . In our series, rituximab was administered as first‐line choice only in 14% of patients at presentation, similarly to the main centers in North America (reviewed by Mazepa et al) 6,9 . We also observed a higher incidence of administration of rituximab as second‐line therapy intended to treat refractoriness or exacerbations, reflecting the more aggressive immunosuppressive approach also used by other groups aimed to prevent further relapses 10,23 .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Rituximab is commonly used to treat mainly refractory and relapsed iTTP patients 10 . In our series, rituximab was administered as first‐line choice only in 14% of patients at presentation, similarly to the main centers in North America (reviewed by Mazepa et al) 6,9 . We also observed a higher incidence of administration of rituximab as second‐line therapy intended to treat refractoriness or exacerbations, reflecting the more aggressive immunosuppressive approach also used by other groups aimed to prevent further relapses 10,23 .…”
Section: Discussionsupporting
confidence: 59%
“…Disease management varies according to centers and countries 7‐10 . In Spain, the public health system offers universal coverage to 99.1% of the population, 11 and hematology departments routinely offer an integrated diagnostic and therapeutic approach to patients with any type of hematological disorder.…”
Section: Introductionmentioning
confidence: 99%
“…However, this proposed superiority in efficacy was not demonstrated in a randomized trial of 27 patients conducted by the North American TTP group (15). Furthermore, as cryosupernatant is not readily available in most US institutions, including ours, our clinical experience is limited as compared to our Canadian colleagues who tend to favor cryosupernatant over FFP in the management of TTP (16,17).…”
Section: Discussionmentioning
confidence: 90%
“…As the first-line treatment, TPE can replenish ADAMTS13 and block microvascular thrombosis [13]. It has been reported that several types of plasma products could be used as the replacement fluid in TPE for patients with TTP [59, 1619]. CP lacking vWF contains an equivalent amount of ADAMTS13 to FFP or its derivative and is considered a better choice than other plasma products, such as FFP, for TPE in patients with TTP [13].…”
Section: Discussionmentioning
confidence: 99%